Analisis Tingkat Kepuasan Pasien Rawat Inap terhadap Pelayanan Kefarmasian di Instalasi Farmasi RS X Tahuna - Gayatri Citraningtyas; Imam Jayanto; Jesica Nangaro; Alfred Nangaro (Faculty of Pharmacy, Universitas Gadjah Mada)
The level of satisfaction achievement on the services provided to patients, both the quality of health services and the health care system, will be the first choice for patients to visit the hospital. The objective of this study was to determine inpatients satisfaction level in the internal diseases room on drug services at Pharmacy Installation Hospital of X Tahuna. This research was a descriptive research with crosssectional design. The research instrument was a form of a questionnaire of hope and reality which was adopted from Nangaro in 2019. The validity and reliability test of the questionnaire was conducted on 30 respondents and data analysis using index of total quality service. There are 115 people who have met the inclusion criteria, such as being willing to be a respondent, being able to read and write, aged ≥ 18 years old, and were currently undergoing treatment in the interna room and have received service at X Tahuna Hospital. Analysis of satisfaction data was using the Weighted Servqual model. The results showed an overall satisfaction index of -0.20, while the satisfaction index for each dimension was as follows: -0.29 for the tangibles dimension, -0.278 emphaty dimensions, -0.17 reliability dimensions, -0.274 dimensions responsiveness, and - 0.32 for the assurance dimension. The overall satisfaction index as well as each dimension shows a negative value, which means that the patient is not satisfied with the drug services at X Tahuna Hospital Pharmacy Installation. The Hospital must re-evaluate the number of human resources (pharmacist-patient ratio), the flow of drug services, as well as the completeness of the available facilities.